A comparative study of safety climate differences in healthcare and the petroleum industry. (18th October 2010) - Olsen, Espen; Aase, Karina
Abstract : Aim: The aim of this article is to compare safety climate in healthcare and the petroleum industry by collecting empirical evidence of differences between the two sectors. Methods: The Hospital Survey on Patient Safety Culture (HSOPSC) is used to measure the safety climate in two organisations operating in the two different sectors: (1) a large Norwegian university hospital offering a wide range of hospital services and (2) a large Norwegian petroleum company producing oil and gas worldwide. Results and discussion: Statistical analyses supported the expected hypotheses that safety climate is positively related to outcome measures and that the level on safety climate and outcome measures are generally higher in the petroleum sector. Empirical findings indicate that healthcare should learn from the petroleum industry regarding safety improvement efforts, and the implication of this is discussed in the paper.